Pemeliharaan dan Pengelolaan Harta Dalam Perspektif Sufistik - Bambang Irawan (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2016)
This paper explains that in order to actualize the teachings of Sufism in the current context must be accompanied by an elastic attitude regarding his teachings. In that sense should be no interpretation in line with giving new insights on the teachings of Sufism such as: ascetic, and resignation. The Sufis over the world looked like fire, where they can take advantage of limited needs, while remaining aware of the spark that will someday burn scorch everything. In this case they said: “If the property is collected, it should be to meet the obligations that must be met, and not for personal gain excessive”. Being a Sufi is not to be poor and the needy, but if God gave them the ordeal in the form of poverty mean He is happy with the condition and they remain grateful for whatever was offered by him. The glory of man in God’s eyes is not located on a lot or a little treasure but how his heart could always remember God day and night, hushed and crowded, thick and thin so any condition does not affect him to continue to draw closer to Him.